Evaluation of Blood Elements and Red Blood Cell Indices Among Sudanese Cannabis and Cigarette Smokers in Khartoum State (Global Journal of Medical Research, 2021)
Background: Cannabis, also known as (marihuana), is a psychoactive drug from the cannabis plant used for medical or recreational purposes. It is one of the most commonly used psychoactive drug worldwide, and it is the most popular illegal drugs. Long-term use of cannabis has acute effects on hemostasis of the body and hematological parameters of addicted individuals. Cigarette smoking is one of the major leading causes of death throughout the world: smoking has both acute and chronic effects on hematological parameters; many studies proved its harmful effects on many organ systems, mainly respiratory, reticuloendothelial system, and cardiovascular systems. Tobacco cigarette smoking is one of the main leading causes of death worldwide. Continuous cigarette smoking has severe adverse effects on hematological parameters (e.g., hemoglobin, white blood cells count, mean corpuscular volume, mean corpuscular hemoglobin concentration, red blood cells count, hematocrit).
Keywords: cannaibs; cigarette cannaibs smokers; hematological parameters